THE EFFECTIVENESS OF PROJECT-BASED WORKSHEETS TO IMPROVE STUDENTS’ NATURAL SCIENCE CONCEPT UNDERSTANDING IN ELEMENTARY SCHOOL - Asfa Zulfiyah (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
Abstract: A teacher still becomes a role model in providing a source of science and knowledge in the classroom in Indonesia up to now. Students become inactive and quickly bored during the learning process. It was due to the teacher’s teaching style that still uses traditional and less innovative. This research attempts to ascertain the effect of project-based worksheets on elementary school students’ natural science concept understanding. The research method uses a post-test-only control design of experimental quantitative research. The population in this research involved the second-grade students of SDI Miftahul Huda. There are two samples, which consist of 24 students of class IIA in the control and 24 students of class IIB in the experimental class. The data analysis used in this research is the independent sample t-test, normality testing, and homogeneity testing. As a result, a sig value (2-tailed) is 0.000 < 0.05, which means H0 is disaccepted and H1 is accepted. In addition, a significant difference between the control and experimental classes was discovered. Thus, project-based worksheets can help elementary school students to improve their understanding of natural science concepts.